Conservation of the endangered Grevy’s zebra: the influence of land use patterns on distribution and abundance in the Samburu–Laikipia landscape, Kenya - Kirathe, Joseph Nderitu; Rubenstein, Daniel I. (Frontiers in Conservation Science, 2025)
The seasonal distribution and abundance of Grevy’s zebra were studied in the Samburu–Laikipia landscape. The aim was to understand how anthropogenic activities combined with seasonal weather patterns influence Grevy’s zebra abundance and distribution. Distance sampling was used to estimate Grevy’s zebra and cattle densities while vegetation structure and composition were measured using selected random line transects. Our analysis showed non-uniform distributions of Grevy’s zebra across the Samburu–Laikipia ecosystem largely driven by seasonal changes in vegetation quality and quantity driven by seasonal rainfall patterns and pastoralist herder use. Grevy’s zebras were found at higher densities and larger herds on community lands during wet periods when livestock grazing was heavy, stimulating grass growth and producing short, high-quality swards. During dry periods, Grevy’s zebras moved to protected areas, commercial ranches, and conservancies where lower levels of year-round grazing produced tall grass banks composed of swards of low-quality vegetation that zebras as hindgut fermenters can process. This suggests that pastoralist herd activity in conjunction with season rainfall patterns shapes Grevy’s zebra movements at a landscape level. While most reproductive classes of Grevy’s zebras occurred together in large herds during the wet season mostly on pastoral grazing lands, during dry periods, only territorial males, lactating females, and their foals were found together with herds that tended to be small. Bachelor males, non-lactating females, and juveniles generally spread themselves evenly over the landscape, perhaps as a way of reducing competition during times of food scarcity or to secure mating. Conservation strategies for successfully increasing survival of all Grevy’s zebra age classes will require maintaining a mixture of rapidly growing grass swards during the wet season and grass bank reserves during the dry season at the regional scale in order to enable seasonal movements across land use patterns driven by alternating rainfall periods. In the past, people have been perceived as part of the “Grevy’s zebra problem”. We show, going forward, that they can become part of the solution.